A currency union in East Asia - Jong-Wha Lee; Yung Chul Park; Kwanho Shin (Osaka University, Institute of Social and Economic Research (ISER), 2003)
This paper investigates prospects of a currency union in East Asia, focusing on trade and financial integration occurring in the region. We find, based on a dynamic factor model, regional common shocks have been quantitatively important for output variations in the Asian economies. We expect that continuing trade integration in the region will lead to further synchronization of business cycles, thereby encouraging East Asian countries to create a currency union in the region. In contrast to trade, however, financial liberalization in East Asia tends to lead to more global integration, rather than regional integration, of the financial systems, and thereby is not likely to develop favorable conditions for forming a regional currency union among East Asian countries.
Keywords: 330; Währungsunion; Regionale Wirtschaftsintegration; Optimaler Währungsraum; Theorie; Ostasien; Makroökonomischer Einfluss